GE_GERICHTE C/17272/2017 vom 2. Oktober 2017 - GE Cour de justice (2017)
PLACEMENT À DES FINS D'ASSISTANCE ; COMPÉTENCE RATIONE LOCI ; DANGER(EN GÉNÉRAL) | CC.426.1:LDIP.85.2:CLAH00.5:CLAH00.10:CLAH.11